Are relative educational inequalities in multiple health behaviors widening? A longitudinal study of middle-aged adults in Northern Norway - Ibarra-Sanchez, Ana Silvia; Chen, Gang; Wisløff, Torbjørn (Frontiers in Public Health, 2023)
Introduction Educational inequality in multiple health behaviors is rarely monitored using data from the same individuals as they age. The aim of this study is to research changes in relative educational inequality in multiple variables related to health behavior (smoking, physical activity, alcohol intake, body mass index), separately and collectively (healthy lifestyle), among middle-aged adults living in Northern Norway. Methods Data from adult respondents aged 32–87 in 2008 with repeated measurements in 2016 (N = 8,906) were drawn from the sixth and seventh wave of The Tromsø Study. Logistic regression was used to assess the relative educational inequality in the variables related to health behavior. The analyses were performed for the total sample and separately for women and men at both baseline and follow-up. Results Educational inequality was observed in all the variables related to health behavior at baseline and follow-up, in both men and women. Higher levels of educational attainment were associated with healthier categories (non-daily smoking, physical activity, normal body mass index and a healthy lifestyle), but also with high alcohol intake. The prevalence of daily smoking and physical inactivity decreased during the surveyed period, while high alcohol intake, having a body mass index outside of the normal range and adhering to multiple health recommendations simultaneously increased. The magnitude of relative educational inequality measured at baseline increased at the follow-up in all the variables related to health behavior. Differences were larger among women when compared to men, except in physical inactivity. Conclusion Persistent and increasing relative disparities in health behavior between the highest education level and lower education levels are found in countries with well-established and comprehensive welfare systems like Norway. Addressing these inequalities is essential for reducing both the chronic disease burden and educational disparities in health.